Effects of hypoxia and reoxygenation on energy metabolism, immune response, and apoptosis in orange-spotted grouper (Epinephelus coioides) - Wu, Yuxin; Lin, Yiran; Lin, Bing; Huang, Yukun; Yu, Zhide; Ma, Yonghao; Feng, Yuwei; Chen, Qiaoyi; Gao, Along; Shu, Hu (Frontiers in Marine Science, 2024)
Hypoxia is an unfavorable environmental condition that produces diverse negative effects in fish. High-density cultures of Epinephelus coioides are more likely to experience hypoxic conditions than those in natural environments. To assess the effects of hypoxia on E. coioides, we examined the related enzyme activities and gene expression after 48 h of hypoxia and 24 h of dissolved oxygen (DO) recovery. Under hypoxic stress (DO: 1.2 ± 0.1 mg/L), the energy supply mode of fish changed from aerobic metabolism to anaerobic metabolism and the serum glucose content and lactate dehydrogenase activity were significantly up-regulated. Total protein, hepatic glycogen, and two key regulatory enzymes (i.e., hexokinase and pyruvate kinase) were differentially expressed in liver, and mRNA expression of three genes (i.e., LDHA, GLUT1, and MCT2) also showed a high expression trend. In serum, three immunerelated enzymes (i.e., alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase) were found to be involved in regulation by hypoxia and showed different levels of changing patterns. Expression of inflammatory genes (i.e., IFNγ, MyD88, were significantly regulated in liver. With prolongation of hypoxic stress, high expression of apoptotic genes (i.e., p53, Bax, Bcl-2, and Caspase-9) was closely related to the degree of apoptosis in liver. Our investigation of the changes in energy metabolism, immune response, and apoptosis of E. coioides under hypoxia and reoxygenation (DO: 6.0 ± 0.1 mg/L) provides a theoretical bases for healthy aquaculture and selection of varieties with tolerance to hypoxia.